Erectile dysfunction. Issue 5 (May 2014) - Russell, Andrew; Ecclestone, Hazel; Kavia, Rajesh
Erectile dysfunction is a persistent or recurrent difficulty maintaining or achieving an erection sufficient for satisfactory sexual activity. It is one of the most commonly reported sexual dysfunctions in men and can have a dramatic impact on the quality of life of the individual and his partner's. Erectile dysfunction has a high prevalence and is an important marker of cardiovascular risk. There are many treatment options available and treating this symptom improves quality of life, well-being and can reduce the risk of subsequently developing cardiovascular disease.